The effectiveness of a knowledge graph-based lifestyle intervention recommendation system in improving body composition, muscle strength, and physical function in sarcopenic obesity: Study protocol for a randomized controlled trial - Xiaohong Liu; Yuxuan Lu; Meiling Fu; Zhenzhen Huang; Ting Shi; Jie Zou; Yinqin Zhong; Yun Chen (PLoS ONE, 2026)
Background Sarcopenic obesity (SO) is a complex condition characterized by the coexistence of sarcopenia and obesity, with pathophysiological mechanisms extending beyond the additive effects of either condition alone. Lifestyle intervention is considered an effective management strategy for SO; however, substantial interindividual variability in physiological status and behavioral preferences limits the implementation of personalized intervention. This study aims to evaluate the effectiveness of a knowledge graph-based lifestyle recommendation system in improving skeletal muscle mass and related outcomes in patients with SO. Methods This randomized controlled trial will recruit 208 patients with SO, who will be randomly assigned in a 1:1 ratio to an intervention or control group. In addition to routine lifestyle guidance, the intervention group will receive a 24-week personalized intervention delivered through the Sarcopenic Obesity-Knowledge Graph Care System (SO-KGCS), whereas the control group will receive routine health education and lifestyle advice only. The intervention period is defined as the 24-week intervention period from baseline to week 24. The primary outcome measure is skeletal muscle mass. Secondary outcome measures include grip strength, skeletal muscle mass index, body fat percentage, physical function, and quality of life. Outcomes will be assessed at baseline before randomization and at weeks 8, 16, and 24 during the 24-week intervention period. The intervention will end at week 24, after which participants will enter a 24-week post-intervention follow-up period without systematic intervention. Follow-up outcome data will be collected at week 48. Discussion This study will evaluate the effectiveness of a knowledge graph-based recommendation system in enhancing body composition, muscle strength, physical function, and quality of life in patients with SO. If effective, the SO-KGCS may provide a feasible intelligent approach for personalized chronic disease management. Trial registration ChiCTR, ChiCTR2500111882.